Pengaruh Investasi, PDRB, UMR, Jumlah UKM Terhadap Penyerapan Tenaga Kerja Sektor UKM Pulau Sumatera - Arifin, Samsul (Jurnal Ilmu Ekonomi JIE, 2023)
This study aims to increase the growth or increase in the level of small and medium enterprises on the island of Sumatra. research using panel data analysis tools. From the research that has been done, it can be concluded that the results of most of the variables are positive, but not with small business units or UMKM, this is because the majority of the population or people on the island of Sumatra work in the mining or plantation sector. The conclusion from this study is that the variables UMKM, PDRB, UMR, Investment have a simultaneous effect on employment. And these variables have no partial effect on employment absorption.